PERAN ZAKAT DAN PENGELOLAAN WAKAF DALAM KEBIJAKAN FISKAL - Fauzi Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
Zakat is an obligation that must be fulfilled by every Muslim. It is this obligation that encourages them to explore the intentions behind the law. At present, zakat has been formulated as an Islamic economic instrument that will provide an even distribution of wealth to fellow Muslims. Zakat is used as a fiscal policy by the government of Islamic countries. Waqf is a religious institution in Islam that has a direct functional relationship with efforts to solve social and humanitarian problems such as poverty alleviation and economic empowerment of the people. Waqf is one of the Islamic financial instruments apart from zakat. If managed productively, it can be used to improve people's living standards. Some interests such as worship, education, socio-economic welfare are actually inherent in the function of waqf. This means that waqf must be managed productively so that waqf really becomes a source of funding from the ummah for the ummah, both for religious, social, and economic interests. For this reason, an understanding of the function of waqf needs to be socialized and become a collective movement for all people in the context of injecting the economy of the people.